The empirical evaluation of thermal conduction coefficient of some liquid composite heat insulating materials; IOP Conference Series: Materials Science and Engineering; Vol. 116 : Advanced Materials and New Technologies in Modern Materials Science - Anisimov M. V.; Rekunov V. S.; Babuta M. N. Marina Nikolaevna; Nguyen Thi Hong Bach Lien (2016, 2016)
Title screen